Duganella albus sp. nov., Duganella aquatilis sp. nov., Duganella pernnla sp. nov. and Duganella levis sp. nov., isolated from subtropical streams in China. Issue 6 (27th June 2020) - Lu, Huibin; Deng, Tongchu; Liu, Feifei; Wang, Yonghong; Yang, Xunan; Xu, Meiying
Abstract : Six Gram-stain-negative, catalase- and oxidase-positive, rod-shaped and motile strains (FT9W T, FT25W, FT26W T, FT109W T, FT134W and CY42W T ) were isolated from subtropical streams in China. Comparisons based on 16S rRNA gene sequences showed that the six strains shared similarities of less than 98.1 % with other species within the family Oxalobacteraceae and formed two separately distinct clades in phylogenetic trees. The 16S rRNA gene sequence similarities between strains FT9W T and FT25W, and between strains FT109W T and FT134W were both 99.7 %. The genome sizes of strains FT9W T, FT25W, FT26W T, FT109W T, FT134W and CY42W T were 6.45, 6.45, 6.54, 6.43, 6.52 and 6.74 Mbp with G+C contents of 64.0, 64.0, 63.8, 63.2, 63.2 and 62.5 %, respectively. The calculated pairwise average nucleotide (ANI) values among the six strains and other related species were less than 93.9 %, except that the values were 99.9 % between strains FT9W T and FT25W, 98.2 % between strains FT109W T and FT134W, and 95.0 and 95.1 % between strain FT26W T and strains FT9W T and FT25W, respectively. However, strain FT26W T shared 16S rRNA gene sequence similarities of only 98.3 and 98.2 % with FT9W T and FT25W, respectively. The respiratory quinone of the six strains was determined to be Q-8. The major fatty acids were C16 : 1 ω 7 c, C16 : 0 and C12 : 0 . The predominant polar lipids included phosphatidylethanolamine and phosphatidylglycerol. Considering the phenotypic, biochemical, genotypic and ANI data, strains FT9W T and FT25W, and FT109W T and FT134W may belong to the same species, respectively. Although the pairwise ANI values between strain FT26W T and each of strains FT9W T and FT25W were located in the transition region of species demarcation, the dissimilarities among them indicated that strain FT26W T could represent an independent novel species. The reconstructed phylogenomic tree based on a concatenation of 92 core genes showed that the six strains clustered closely with Duganella sacchari Sac-22 T and Duganella radicis KCTC 22382 T, and supported that these six strains belong to the genus Duganella . The names Duganella albus sp. nov. (type strain FT9W T =GDMCC 1.1637 T =KACC 21313 T ), Duganella aquatilis sp. nov. (type strain FT26W T =GDMCC 1.1641 T =KACC 21315 T ), Duganella pernnla sp. nov. (type strain FT109W T =GDMCC 1.1688 T =KACC 21480 T ) and Duganella levis sp. nov. (type strain CY42W T =GDMCC 1.1673 T =KACC 21465 T ) are proposed.